2012
DOI: 10.1523/jneurosci.5365-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Axonal Topology on the Somatic Modulation of Synaptic Outputs

Abstract: Depolarization of the neuronal soma augments synaptic output onto postsynaptic neurons via long-range, axonal cable properties. Here, we report that the range of this somatic influence is spatially restricted by not only axonal path length but also a branching-dependent decrease in axon diameter. Cell-attached recordings of action potentials (APs) from multiple axon branches of a rat hippocampal CA3 pyramidal cell revealed that an AP was broadened following a 20 mV depolarization of the soma and reverted to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 32 publications
3
65
0
Order By: Relevance
“…The shape of on-cell transients ( Fig. 1A2) represents a combination of inversion and the time derivative of intracellular counterparts (Sasaki et al 2012). Whole cell access to the terminal, with a holding potential of Ϫ80 mV, gave rise to a holding current of Ϫ250 pA.…”
Section: Resultsmentioning
confidence: 99%
“…The shape of on-cell transients ( Fig. 1A2) represents a combination of inversion and the time derivative of intracellular counterparts (Sasaki et al 2012). Whole cell access to the terminal, with a holding potential of Ϫ80 mV, gave rise to a holding current of Ϫ250 pA.…”
Section: Resultsmentioning
confidence: 99%
“…Hybrid analog-digital enhancement of synaptic transmission at spiking synapses initially described in invertebrates [29,37,39,40] has been more recently reported in many mammalian synapses of the CNS including cortical [24,42,48], cerebellar [9,12], and hippocampal excitatory synapses ( [1,18,34]; Bialowas et al, 2014). In these examples, synaptic transmission evoked by single APs is enhanced as the result of analog-mediated depolarization (10-30 mV) of the presynaptic element for a few tens to hundreds of milliseconds (Fig.…”
Section: Analog-digital Signaling: Analog Signaling At Spiking Synapsesmentioning
confidence: 93%
“…In L5 pyramidal neurons, ADF is observed after several seconds of presynaptic depolarization [24,42] whereas a few tens of milliseconds of analog subthreshold depolarization is sufficient to induce ADF at mossy fiber-CA3 cell synapses [1] or at cerebellar GABAergic synapses [9]. At CA3-CA3 connections, the temporal requirement of ADF is not clear [34].…”
Section: Analog-digital Signaling: Analog Signaling At Spiking Synapsesmentioning
confidence: 99%
“…We therefore investigated the possibility that subthreshold synaptic inputs may modify the shape of action potentials as they propagate along the dendron. Previous studies in hippocampal neurons have demonstrated that subthreshold depolarizations in the axon can broaden action potentials leading to changes in neurotransmitter release [32,33,34,35]. To investigate whether this occurs in GnRH dendrons, we focally uncaged glutamate while recording dendritic spikes with an on-cell recording electrode.…”
Section: Multitasking In the Dendronmentioning
confidence: 99%
“…It is important to note however that this effect on the shape of the spike will only be localized to the region of the dendron where the synaptic input occurs. At regions further down the projection, where the depolarization will be very small or negligible, the impact on spike shape will cease to exist [33]. Therefore, current evidence suggests that synaptic inputs onto this central region will not impact excitability either at the spike initiation site or the nerve terminals.…”
Section: Functional Role Of a Mixed Dendritic-axonal (Dendron) Projecmentioning
confidence: 99%